What We See and Why We Stay: Place Studies Through Windshield Surveys of Scott County, Kansas - Davis, Macy (Kansas State University, The Chapman Center for Rural Studies, 2017)
The western plains of Kansas sweep from one end of the horizon to another seemingly without ending. They are broken only by the sharp asphalt of highways cutting through fields and pastures which connect the numerous small towns that dot the prairie. Family vehicles, Semi-trucks, and farm implements are not uncommon sights, often waiting to turn onto highways from gravel roads. Scott County sits solidly in western Kansas, two counties away from the Colorado border and not far enough in either direction to be classified as south-western or north-western .
Macy Davis, “What We See and Why We Stay: Place Studies Through Windshield Surveys of Scott County, Kansas,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/253.
Keywords: Interstate 70; landscape; place study; Scott City; Scott County; windshield survey